Macroeconomics, Third Edition - Tuerck, David (Issn Ser., 2021)
The task of macroeconomics is to provide the tools for understanding the performance of the aggregate economy, as measured by production, employment, inflation, and other economic indicators. Most books on this topic compare different theories of macroeconomic performance, under alternative assumptions about how individual consumers, workers and investors adjust to the economic environment in which they find themselves. This book brings these theories together under one methodological roof, where the choices made by economic agents depend on their varying perceptions of the economic constraints they face, combining new classical principles, under which the economy operates at full employment, with theories that allow for extended periods of underemployment brought about by mixed signals from workers and employers. The book takes up modern monetary theory and its bearing on the massive deficits run up the federal government over the ongoing 'corona contraction' and the earlier 'great contraction'. Thee author also reviews the policy interventions undertaken by the federal government during these contractions, with a view toward assessing their effectiveness.